Multimarker assessment for the prediction of renal function improvement after percutaneous revascularization for renal artery stenosis - Staub, Daniel (Cardiovasc Diagn Ther, 2016)
BACKGROUND: Identifying patients likely to have improved renal function after percutaneous transluminal renal angioplasty and stenting (PTRA) for renal artery stenosis (RAS) is challenging. The purpose of this study was to use a comprehensive multimarker assessment to identify those patients who would benefit most from correction of RAS. METHODS: In 127 patients with RAS and decreased renal function and/or hypertension referred for PTRA, quantification of hemodynamic cardiac stress using B-type natriuretic peptide (BNP), renal function using estimated glomerular filtration rate (eGFR), parenchymal renal damage using resistance index (RI), and systemic inflammation using C-reactive protein (CRP) were performed before intervention. RESULTS: Predefined renal function improvement (increase in eGFR ≥10%) at 6 months occurred in 37% of patients. Prognostic accuracy as quantified by the area under the receiver-operating characteristics curve for the ability of BNP, eGFR, RI and CRP to predict renal function improvement were 0.59 (95% CI, 0.48–0.70), 0.71 (95% CI, 0.61–0.81), 0.52 (95% CI, 0.41–0.65), and 0.56 (95% CI, 0.44–0.68), respectively. None of the possible combinations increased the accuracy provided by eGFR (lower eGFR indicated a higher likelihood for eGFR improvement after PTRA, P=ns for all). In the subgroup of 56 patients with pre-interventional eGFR <60 mL/min/1.73 m(2), similar findings were obtained. CONCLUSIONS: Quantification of renal function, but not any other pathophysiologic signal, provides at least moderate accuracy in the identification of patients with RAS in whom PTRA will improve renal function.